La lande basse à Diapensia lapponica de l'archipel de Saint-Pierre et Miquelon et sa signification biogéographique - MULLER, Serge (Société nationale de protection de la nature et d'acclimatation de France, Paris (FRA), 2008)
The summits of Saint-Pierre and Miquelon archipelago are colonized by a plant community of open low heathland, whose plant composition shows a high concentration of nano-chamaephytes with arctic-alpine distribution, such as Arctostaphylos alpina, Diapensia lapponica, Loiseleuria procumbens and Salix uva-ursi. This plant community can be classified in the achionophitic alliance Loiseleurio-Diapension, which is a typical unit of arctic tundra (Alaska, Labrador, Greenland, Iceland, Lapland, northern Siberia). In more southern areas dominated by boreal or temperate forests, this unit occurs on high summits (for instance Mounts Otish in the Laurentides, Mounts Chic-Chocs in Gaspésie, Mounts Washington in New Hampshire), where it characterizes an alpine tundra habitat. The occurrence on the summits of Saint-Pierre and Miquelon archipelago of this Diapensia lapponica and Loiseleuria procumbens community assesses their natural asylvatic character during the postglacial period. It constitutes an arctic-alpine tundra community, which surmounts the boreal forest with Abies balsamea. This remarkable altitudinal zonation expresses the transition character of the archipelago vegetation between boreal and arctic bioclimatic areas.